Firms in Product Space: Adoption, Growth and Competition - Luca Macedoni; John Morrow; Vladimir Tyazhelnikov (CESifo GmbH, 2024)
Which products are potentially produced together? When demand for a product increases, which firms will supply it? Using multi-product production patterns within and across firms, we recover a continuous cost-based distance between firms and unproduced products. Higher product distance implies decreasing adoption frequency. When export demand induces domestic product adoption, closer firms provide this supply. Potential costs imply measures of Revenue and Competition Potential. These predict firm sales and scope growth. If all firms produced all products linked by co-production, consumer welfare could increase by 16-30% under constant markups, rising to 46-86% under variable markups.
Keywords: F10; D20; L10; L23; L25; 330; multi-product firms; firm capabilities; product classification; product space; growth paths